The Relationship Between the Fractal Dimension and the Evolution of Rock-Forming Minerals Crystallization on the Example of the Northwestern Part of the Lovozero Intrusion - Miłosz Huber; Klaudia Stępniewska; Mirosław Wiktor Huber (Fractal and Fractional)
This article presents the results of fractal texture analyses of selected minerals (aegirine, eudialyte, orthoclase) in the northwestern part of the Lovozero intrusion. This intrusion is located in northeastern Scandinavia and is a massif made of alkaline rocks. There are rocks such as massive syenites and porphyrtes, as well as iiolites, urtites, and foyaites, accompanied by metasomatic rocks of the contact zone. A box-counting fractal dimension was used to numerically represent the texture of these minerals. In the further part, this coefficient was visualized in the form of maps superimposed on the study area, and some simple arithmetic calculations were performed to highlight the common features of this dimension for the selected rock-forming minerals. In conjunction with the geological interpretation of these results, rock-forming processes in this massif were depicted. This work is preliminary, showing the potential of this calculation method in petrological applications.